Study on the thermal and electrical properties of novel poly[propyl acrylate-co-phenyl methacrylate] containing acetamido group - Biryan, Fatih; Pihtili, Guzin (Springer, 2021)
In the available research, firstly a new 3-acetamido phenyl acrylate (APhA) monomer and a novel copolymer containing acetamido phenyl group were synthesized. 3-acetamido phenyl acrylate (APhA) monomer was acquired by the reaction of acryloyl chloride and N-(3-hydroxyphenyl) acetamide. 3-acetamido propyl methacrylate (AAPMA) monomer was prepared in our previous study. A series of copolymers were prepared using these monomers in different mole ratios by free-radical polymerization method at 70 degrees C The structure of P(AAPMA-co-APhA) copolymer systems was characterized by FT-IR and NMR techniques. Thermal characteristics of P(AAPMA-co-APhA) copolymers were evaluated through thermogravimetric analysis (TGA) and differential scanning calorimeter (DSC) in an N-2 atmosphere. Due to the presence of the amide group, we can say that the polymer with the least weight loss and the highest residue percentage at 500 degrees C is poly(APhA). AC electrical conductivity and dielectric and electrical parameters were analyzed in a range of 100 Hz-20 kHz frequency. The dielectric constant values of poly(AAPMA-co-APhA0.63) and P(AAPMA-co-APhA0.30) were 4.98 and 4.57 respectively. According to the results, the dielectric value decreased as the APhA units increased.
Keywords: New monomer synthesis; Thermal properties; Dielectric behavior; Dielectric properties